Analysis of Internal Control of Cash Receipt and Disbursement Functions at Unggul Polytechnic LP3M Medan - Martin Martin; Purjianto Purjianto; Mahyudin Mahyudin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Cash is the company's most liquid asset and plays a significant role in funding the company's operations compared to other investments, so cash control is needed within the company. Companies with organizational management where internal controls can control errors in carrying out the profession to protect cash from misuse efforts from when cash is received until it is disbursed. LP3M Superior Polytechnic is a private tertiary institution whose primary income is the payment of student tuition fees. The research method uses the descriptive analysis method. The test results show that the cash receipts internal control system is effective, contrary to the cash disbursement internal control. At the same time, the internal control system for cash disbursements has not been effective because there are still elements of Internal Control within the company that have not been fully implemented, including placing the cashier in the same room as other employees, which should be separate and have a separate room as accounting control.